Desarrollo de una ruta estratégica que relaciona la proporción carbono nitrógeno (C/N) alimentado al cultivo de Chlamydomonas reinhardtii con la calidad de biodiesel (2016)
For the realization of the degree proposed a system of treatment of pure water for the aqueduct water of the Trapiche S.A.S, in Villavicencio, Meta, from a well deep concession of his property, the company gave the initial characterization of the water, which was compared with current regulations, which highlighted four parameters that failed; These amount of iron, color, turbidity and free chlorine residual. The sum of these parameters with carried a high risk index is not apt for human consumption. Based on these parameters, was a bibliographic comparison chart with pros, cons and applicability in order to evaluate the possible treatment options for these parameters in particular. We gave a percentage for the evaluation for any parameters which are very important to complete the Colombian rules, and important for the company. After the selection of the alternative of treatment was to corroborate this election through an experimental laboratory practice. This was based on the simulation of the process of clarification by the test of pitchers, thus obtaining the right dosage for the treatment of water.